Fundamentals of sport management - Baker, Robert E. 1957-; Esherick, Craig (Champaign, IL Human Kinetics, 2013)
Fundamentals of Sport Management presents foundational knowledge of sport management and what sport managers do to help readers prepare for advanced study or practice in the field. An excellent reference for students or professionals, Fundamentals of Sport Management offers insights into the exciting field, the impact of the sport industry, and the possibilities for employment in sport. Written by an author team with experience in both the academic world and sport industry, Fundamentals of Sport Management combines introductory concepts with practical information in sport management. The text begins with a discussion of the origins and development of the field, professional associations, essential components of professional preparation, and potential paths to employment. The various chapters in the text cover everything from managerial principles and sport policy to marketing, economics, and ethics in sport. By presenting an overview of the areas involved in sport management, the text allows readers to focus their efforts to prepare for further study, research, and career opportunities. Throughout the text, unique learning features keep readers engaged with the content and focused on key information: Chapter objectives and opening scenarios introduce important concepts in each chapter; Management Insights explain the background of relevant sport management issues; Quick Facts highlight surprising facts about sport management; International Application sidebars detail the global significance of and global applications for sport business; Success Story segments profile individuals working in sport management; Quotes offer meaningful insights from experts in the field; The Short of It sections present summaries at the end of each chapter. Appendixes include a list of online and print resources for further study as well as tips on applying the principles of sport management to various positions in the sport industry. These features and resources will help build enthusiasm among readers and open their eyes to the opportunities in the field. Concise, informative, and practical, Fundamentals of Sport Management addresses the academic foundations of the field for a broad audience while providing real-world examples of sport management. This resource is ideal for those engaging in the field of study for the first time (such as high school and undergraduate students) or those seeking an overview of the career options available in sport management (such as professionals exploring a career change). For practitioners, Fundamentals of Sport Management makes a quick reference for basic information on a range of areas in sport management. This text is part of Human Kinetics' Fundamentals of Sport and Exercise Science series. The series helps students and professionals understand the basic topics, goals, and applications of the many subdisciplines in kinesiology. This and other books in the series provide a solid grounding that readers can use as a jumping-off point for further study.
Part I. Welcome to Sport Management -- Chapter 1. What Is Sport Management? ; Origins in Physical Education, Athletics, and Business ; Sport Management: 1900 to 1965 ; Sport Management: 1966 to 1979 ; Sport Management: 1980 to 1999 ; Sport Management: 2000 and Beyond--Current Status ; Professional Preparation in Sport Management ; Professional Associations in Sport Management ; The Short of It -- Chapter 2. What Can I Do With Sport Management? ; Careers in Sport Management ; Paths to Employment ; Professional Preparation for a Sport Management Career ; Professional Development in Sport Management ; The Short of It -- Part II. Building Blocks of Sport Management -- Chapter 3. Sport Management Principles and Functions ; Organizations in Sport ; Management Functions ; Universality of Management ; Skills, Roles, and Responsibilities of Managers ; The Short of It -- Chapter 4. Leadership in Sport Organizations ; Leadership Versus Management ; The ABCs of Sport Leadership: Antecedents, Best Practices, and Consequences ; Antecedents of Leadership ; Sport Organizations as Systems ; Best Practices: The Art and Science of Leadership ; Consequences of Leadership ; The Short of It -- Chapter 5. Sport Policy and Governance ; What Is Good Governance? ; What Is Governance in Sport? ; Governance of High School Sport ; Governance of Collegiate Athletics ; Governance of Professional Sport ; The Short of It -- Chapter 6. Sport Venues, Event Management and Building Operations ; Venues ; Event Management, Risk Management, and Crowd Control ; The Short of It -- Chapter 7. Sport Law ; The U.S. Legal System ; U.S. Tort Law ; U.S. Contract Law ; Title IX ; ADA ; Intellectual Property ; Dispute Resolution--Negotiation, Mediation, Arbitration, and Litigation ; The Short of It -- Chapter 8. Sport Marketing ; The Marketing Mix ; What's Unique About Sport Marketing? ; Sport Marketing Plans ; The Short of It -- Chapter 9. Sport Media ; History of Media in Sport ; Traditional Media in the 21st Century ; New Media ; Ethics and Sport Media ; The Short of It -- Chapter 10. Sport Economics ; Macro- and Microeconomics ; The Economics of Sport Leagues ; The Economics of College Athletics ; Outside Influences That Affect Sport Economies ; The Short of It -- Chapter 11. Sport Finance ; Accounting 101 ; Interscholastic Sport Finance ; Intercollegiate Sport Finance ; Finance in Professional Sport ; The Short of It -- Chapter 12. Ethics in Sport Management ; Theoretical Foundations ; Ethical Decision Making ; Ethical Challenges in Sport Management ; The Short of It.
Includes bibliographical references
Keywords: Sports administration